The Potential Of Sustainability Aspects For Development Of Tourism Sector In Central Java - Apri Kuntariningsih; Mengku Marhendi; Yustina Denik Risyanti; Samtono Samtono; Sapto Supriyanto; Andhi Supriyadi; Hartoyo Soehari (International Conference On Digital Advanced Tourism Management And Technology, 2023)
Tourism supports economic development because tourism contributes to the economy of a region. The benchmark for the success of the tourism industry, especially its development, is the increasing number of tourists, both local and foreign, while always paying attention to the sustainability of tourism destinations. This research aims to document and analyze tourism development with indicators of the number of tourist visits, sustainable tourism with environmental aspects through reviewing waste management, and social aspects through the sustainability of cultural heritage in Central Java Province. The research location is in Central Java Province, with aggregate provincial data which shows that in this province tourism villages are being activated and promoted, while this research uses descriptive qualitative. The results of this research show that to reduce dependence on one particular market or tourist segment, market diversification is necessary. In the environmental aspect, it is necessary to provide sanctions for those who litter, strive to use environmentally friendly technology, and involve the private sector in supporting waste management programs. Social aspects by maximizing strengths, taking advantage of opportunities, overcoming weaknesses, and overcoming threats.